Synthesis of Zinc Oxide Nanostructures on Graphene/Glass Substrate via Electrochemical Deposition: Effects of Potassium Chloride and Hexamethylenetetramine as Supporting Reagents - Hambali, Nur Ashikyn; Hashim, Abdul Manaf (Nano-Micro Letters, 2015)
The effects of the supporting reagents hexamethylenetetramine (HMTA) and potassium chloride (KCl) mixed in zinc nitrate hexahydrate (Zn(NO3)2·6H2O) on the morphological, structural, and optical properties of the resulting ZnO nanostructures electrodeposited on graphene/glass substrates were investigated. The supporting reagent HMTA does not increase the density of nanorods, but it does remarkably improve the smoothness of the top edge surfaces and the hexagonal shape of the nanorods even at a low temperature of 75 °C. Hydroxyl (OH−) ions from the HMTA suppress the sidewall growth of non-polar planes and promote the growth of ZnO on the polar plane to produce vertically aligned nanorods along the c axis. By contrast, the highly electronegative chlorine (Cl−) ions from the supporting reagent KCl suppress the growth of ZnO on the polar plane and promote the growth on non-polar planes to produce vertical stacking nanowall structures. HMTA was found to be able to significantly improve the crystallinity of the grown ZnO structures, as indicated by the observation of much lower FWHM values and a higher intensity ratio of the emission in the UV region to the emission in the visible region. Equimolar mixtures of Zn(NO3)2·6H2O and the supporting reagents HMTA and KCl seem to provide the optimum ratio of concentrations for the growth of high-density, uniform ZnO nanostructures. The corresponding transmittances for such molar ranges are approximately 55–58 % (HMTA) and 63–70 % (KCl), which are acceptable for solar cell and optoelectronic devices.